Mechanistic switch in dual gold catalysis of diynes: C(sp3)-H activation through bifurcation-vinylidene versus carbene pathways - Hansmann, Max M.; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2013)
The other side of the mountain: Changing the framework of diyne systems opens up new cyclization modes for dual gold catalysis. Instead of a 5-endo cyclization and gold vinylidenes a 6-endo cyclization gives rise to gold-stabilized carbenes as key intermediates for selective CH insertions.
Die Zahl 3 ist im Titel hochgestellt
Gesehen am 26.01.2021